Neuropsychiatric systemic lupus erythematosus : diagnostic and clinical features according to revised ACR criteria - Buća, Ante (Array, 2009)
Abstract: Neuropsychiatric disorders appear in about 70% of the patients diagnosed with systemic lupus erythematosus (SLE). The aim of this study was to evaluate morphological and functional abnormalities of central nervous system (CNS) in SLE patients with neuropsychiatric manifestations (NP) of disease by testing their relationship. We tested 10 patients (9 females, 1 male) with clinical manifestations of neuropsychiatric systemic lupus erythematosus (NP-SLE). That means clinical evaluation of symptoms, standard immunoserological tests, electroencephalogram (EEG), component of audio-evoked potentials P300, MMPI-202 test, Rey Complex Test and magnetic resonance imaging (MRI). MRI abnormalities were seen in all of our patients, while in 9 patients abnormalities in neuropsychological and neurophysiologic tests have been proved. The most common structural brain change, detected by MRI, was cortical atrophy (in 8 out of 10 patients). According to revised classification of the American College of Rheumatology (ACR) NP-SLE, the most frequent disorder was cognitive dysfunction (in 9 out of 10 patients). Cortical atrophic brain changes have been established in 7 out of 9 patients with cognitive dysfunction. Because of already known correlation of cortical atrophy with cognitive dysfunction in SLE patients, without neuropsychiatric manifestation, we can conclude that neuropsychological examination is required in every patient with systemic lupus erythematosus